2013
DOI: 10.1111/ijcp.12063
|View full text |Cite
|
Sign up to set email alerts
|

Renin-angiotensin system inhibitors for prevention of recurrent atrial fibrillation: a meta-analysis

Abstract: Based on the currently available data, inhibition of RAS is effective, safe and well tolerated for preventing the recurrence of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Although the details remain unclear, the persistence of AF is considered as a result of atrial remodeling, which could in turn contribute to the initiation and development of AF [ 14 ]. LAD enlargement triggers the activation of the renin aldosterone angiotensin system (RAAS) and subsequently lead to increase in matrix metalloproteinases, which result in atrial remodeling and fibrosis, with loss of atrial muscle mass [ 32 ]. In addition, interstitial fibrosis may induce local intra-atrial conduction block and increase atrial susceptibility to AF, as well as forming stable local sources for AF induction [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the details remain unclear, the persistence of AF is considered as a result of atrial remodeling, which could in turn contribute to the initiation and development of AF [ 14 ]. LAD enlargement triggers the activation of the renin aldosterone angiotensin system (RAAS) and subsequently lead to increase in matrix metalloproteinases, which result in atrial remodeling and fibrosis, with loss of atrial muscle mass [ 32 ]. In addition, interstitial fibrosis may induce local intra-atrial conduction block and increase atrial susceptibility to AF, as well as forming stable local sources for AF induction [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of treatment with angiotensin‐converting enzyme inhibitors (ACE‐Is) or angiotensin receptor blockers (ARBs), in the primary or secondary prevention of AF, showed a significant reduction in the risk for AF recurrence after cardioversion with the use of ACE‐Is or ARBs, reducing the odds for secondary AF by 33% . A recent meta‐analysis of 3972 patients with AF showed that inhibition of RAS is effective, safe, and well tolerated for preventing the recurrence of AF …”
Section: Predictors Of Maintenance Of Sinus Rhythm After Successful Cmentioning
confidence: 99%
“…8 A recent meta-analysis of 3972 patients with AF showed that inhibition of RAS is effective, safe, and well tolerated for preventing the recurrence of AF. 9 The left atrial (LA) diameter is a powerful predictor of AF recurrence as shown in more than one AFFIRM (Atrial Fibrillation Follow-up Investigation of Rhythm Management) analysis. 10,11 AF recurrence is more likely to occur within 6 months after a successful cardioversion if left atrial enlargement is present, especially when the (LA) diameter exceeds 5.0 cm.…”
Section: Predictors Of Maintenance Of Sinus Rhythm After Successful Cmentioning
confidence: 99%
“…Angiotensin‐converting enzyme inhibitors and angiotensin receptor blockers are commonly used in all grades of HF and in hypertension. They increase the likelihood of long‐term SR after ECV . However, more research is required, as some studies show no benefit to RAS blockade and they are not recommended for routine use pre‐ECV.…”
Section: Af and Patient Factorsmentioning
confidence: 99%